Professional Caregiving in Motor Neurone Disease: An Exploratory Mixed-Methods Study of Professional Well-Being and Support Needs - Walls, Megan (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
Introduction: Motor neurone disease (MND) is a complex, incurable neurodegenerative condition that imposes profound physical, psychological, and social burdens on affected individuals and their families. In the absence of curative treatments, healthcare professionals play a pivotal role in delivering compassionate, supportive care focused on symptom management and quality of life. While healthcare professional well-being is increasingly recognised as central to the patient experience and workforce sustainability, the experiences of professionals working with people affected by MND remain underrepresented in the literature, with limited understanding of the emotional and psychological impact of this work on their professional well-being or the supports required to sustain them in these roles and in providing compassionate MND care. Aim: This PhD aimed to develop an understanding of the experiences of healthcare professionals working with people living with MND and their families, examine the impact of this work on personal and professional well-being, and inform practical recommendations to support professional well-being and workforce sustainability. Method: An exploratory sequential mixed methods design was employed across four interconnected phases. Phase One comprised a scoping review of the existing literature. Phase Two involved focus groups with healthcare professionals working in MND care in Ireland, analysed using reflexive thematic analysis. Phase Three consisted of a cross-sectional online survey of healthcare professionals providing MND care across Europe. Phase Four integrated findings from the preceding phases using the Extended Pillar Integration Process and informed actionable, practice-relevant recommendations. Results: Phase One synthesised findings from 51 existing sources and found that MND care was perceived as distinctive, more intensive, and highly individualised compared with other patient populations. Healthcare professionals ability to provide optimal care was influenced by patient complexity, informal caregiver involvement, multidisciplinary team support, and organisational context. Although the emotional impact of MND care was evident, professional well-being was not directly measured and was seldom the primary focus of the identified existing literature. Phase Two recruited 43 healthcare professionals across the Irish healthcare system and highlighted the emotionally demanding and relational nature of MND care across the illness trajectory. While clinicians described strong commitment to compassionate, person-centred care, they were also challenged by feelings of uncertainty and helplessness, emotional burden and systemic constraints. Findings identified opportunities for enhanced professional education and development, interpersonal organisational level supports to sustain professional well-being and their ability to deliver consistent, compassionate care. Phase Three found that 67% of 230 European healthcare professionals experienced moral distress in their work with MND patients and families. This was significantly associated with reduced professional quality of life, including higher burnout and secondary traumatic stress, and with intentions to leave or change roles. Despite these challenges, compassion satisfaction was high and negatively associated with burnout, while informal collegial support and multidisciplinary teamwork emerged as key protective factors. Phase four integrated findings across each of the three preceding phases, outlining how healthcare professionals' experiences and well-being can be shaped by multilevel influences spanning system, organisational, interpersonal, and individual domains. Corresponding opportunities for support, education and intervention were identified to enhance professional well-being and professional quality of life in this context. Conclusion: This research has identified that working with people and families affected by MND can both positively and negatively affect the personal and professional well-being of healthcare professionals involved in providing their care. While the practical, emotional and ethical complexities of these roles can place professionals at risk of moral distress, compassion fatigue and burnout, many derive substantial meaning, purpose, and compassion satisfaction from their work. Supporting the well-being of healthcare professionals providing MND care requires multifaceted approaches spanning system and organisational change, interpersonal supports, and individual-level education and intervention. Future work is needed to both develop and test the effectiveness of interventions and approaches aimed at reducing the impact of working with MND on professional well-being and quality of life.
APPROVED
Keywords: Motor Neurone Disease; Healthcare Professionals; Moral Distress; Professional Well-being